Beyond one pill, once daily: current challenges of antiretroviral therapy management in the United States. Issue 12 (2nd December 2019) - Masters, Mary Clare; Krueger, Karen M.; Williams, Janna L.; Morrison, Lindsay; Cohn, Susan E.
ABSTRACT: Introduction : Modern antiretroviral therapy (ART) has revolutionized HIV treatment. ART regimens are now highly efficacious, well-tolerated, safe, often with one multi-drug pill, once-daily regimens available. However, clinical challenges persist in managing ART in persons with HIV (PWH), such as drug–drug interactions, side effects, pregnancy, co-morbidities, and adherence. Areas Covered : In this review, we discuss the ongoing challenges of ART for adults in the United States. We review the difficulties of initiating ART and maintaining therapy throughout adulthood and discuss new agents and strategies under investigation to address these issues. A PubMed search was utilized to identify relevant publications and guidelines through July 2019. Expert Opinion : Challenges persist in initiation and maintenance of ART. An individual's coexisting medical, social and personal factors must be considered in selecting and continuing ART to ensure safety, tolerability, and efficacy throughout adulthood. Continued development of new therapeutics and novel approaches to ART, such as long acting drugs or dual therapy, are needed to respond to many of these challenges. In addition, future research must address therapeutic disparities for populations historically underrepresented in clinical trials, including women, people aging with HIV, and those with complex comorbidities.